History of law and economics - Martin Gelter; Kristoffel Grechenig (Max Planck Institute for Research on Collective Goods, 2014)
The roots of law & economics lie in late 19th century continental Europe. However, this early movement did not persist, having been cut off in the 1930s. After World War II, modern law & economics was (re-)invented in the United States and subsequently grew into a major field of research at U.S. law schools. In continental Europe, law & economics was re-imported as a discipline within economics, driven by economists interested in legal issues rather than by legal scholars. Hence, the European discourse was more strongly influenced by formal analysis, using mathematical models. Today, research in the U.S., Europe, and in other countries around the world, including Latin America and Asia, uses formal, empirical, and intuitive methods. New subfields, such as behavioral law & economics and experimental law & economics, have grown in the U.S. and in Europe during the past two decades.
Keywords: 330